Addressing Constraints and Stategies in Introducing Food Waste Literacy for Indonesian School Children: A Mini Corpus Study - Harmoko, Danang Dwi; Rafli, Zainal; Iskandar, Ifan (Journal of Linguistics, Literacy, and Pedagogy, 2023)
Food literacy and food waste have not received special attention from both the Indonesian government and society. However, considering that the country produces the second largest food waste in the world, ranking 100th at literacy and a stunting prevalence rate of 24.4% in 2021, the introduction and education of students about this issue is very important and urgent. This study aims to determine the urgency, constraints, and strategies for food literacy and food waste for children at school. This research uses a descriptive qualitative approach. Data collection through the study of research literature and relevant information. The results of the study show that the introduction of food literacy and food waste has a high level of urgency considering the environmental impact and future sustainability of Indonesia. Another supporting factor is that Indonesia's 2030 green growth policy can be used as a driver and basis for policy. Then, there are three obstacles to the success of this effort, teacher capacity, culture, policies, and alignments. This research also describes strategies that can be used, literacy school programs, use of interactive educational media, and collaboration with social media influencers and public figures.